Metabolic characteristics of long-lived mice - Bartke, Andrzej; Westbrook, Reyhan (Frontiers in Genetics, 2012)
Genetic suppression of insulin/insulin-like growth factor signaling (IIS) can extend longevity in worms, insects, and mammals. In laboratory mice, mutations with the greatest, most consistent, and best documented positive impact on lifespan are those that disrupt growth hormone (GH) release or actions. These mutations lead to major alterations in IIS but also have a variety of effects that are not directly related to the actions of insulin or insulin-like growth factor (IGF-1). Long-lived GH-resistant GHRKO mice with targeted disruption of the GH receptor gene, as well as Ames dwarf (Prop1df) and Snell dwarf (Pit1dw) mice lacking GH (along with prolactin and TSH), are diminutive in size and have major alterations in body composition and metabolic parameters including increased subcutaneous adiposity, increased relative brain weight, small liver, hypoinsulinemia, mild hypoglycemia, increased adiponectin levels and insulin sensitivity, and reduced serum lipids. Body temperature is reduced in Ames, Snell, and female GHRKO mice. Indirect calorimetry revealed that both Ames dwarf and GHRKO mice utilize more oxygen per gram (g) of body weight than sex- and age-matched normal animals from the same strain. They also have reduced respiratory quotient (RQ), implying greater reliance on fats, as opposed to carbohydrates, as an energy source. Differences in oxygen consumption (VO2) were seen in animals fed or fasted during the measurements as well as in animals that had been exposed to 30% calorie restriction or every-other-day feeding. However, at the thermoneutral temperature of 30°C, VO2 did not differ between GHRKO and normal mice. Thus, the increased metabolic rate of the GHRKO mice, at a standard animal room temperature of 23°C, is apparently related to increased energy demands for thermoregulation in these diminutive animals. We suspect that increased oxidative metabolism combined with enhanced fatty acid oxidation contribute to the extended longevity of GHRKO mice.